Neurocognitive Function and Schizophrenia-Proneness in Individuals Dependent on Ketamine, on High Potency Cannabis (‘Skunk’) or on Cocaine - Morgan, C.J. A.; Duffin, S.; Hunt, S.; Monaghan, L.; Mason, O.; Curran, H. V. (Pharmacopsychiatry, 2012)
Ketamine, psychostimulants and cannabis have all been associated with psychotic phenomena but no study has directly compared users of these drugs.The aim of this study was to assess schizophrenia proneness and neurocognitive function in individuals dependent upon ketamine, cannabis and cocaine.130 volunteers – 29 ‘skunk’ users, 22 cocaine users, 21 ketamine users, along with 28 ‘recreational’ poly-drug users and 30 drug-naïve controls – were assessed on the Schizophrenia Proneness Instrument, Adult version (SPI-A). They were specifically asked to rate symptoms when not under the acute influence of a psychoactive drug.Ketamine and skunk users manifested the greatest attentional and cognitive disturbances. The symptom profile of the dependent ketamine users was very similar to that of prodromal individuals who transitioned to psychosis.Given the recent rapid rise in use of high potency cannabis and of ketamine, these findings are important and clinicians should be careful to rule out the effects of persistent drug use, especially in users of ketamine or skunk, when assessing an individual’s risk of psychosis. A longitudinal study is needed to differentiate which basic symptoms persist following abstention from ketamine and skunk.
Keywords: ketamine; cannabis; cocaine; dependence; prodrome; schizophrenia